Do hotspot policing interventions against optimal foragers cause crime displacement? - Halford, Eric (International journal of law, crime and justice, 2024)
Optimal forager theory (OFT) initially emerged from ecological studies, elucidating how foraging organisms seek resources. In recent decades, this ecological theory has migrated to the realm of criminology, where it is used to identify burglary offenders and inform crime analysis. Several police services employ optimal forager theory-based analysis to guide hotspot patrol interventions aimed at reducing domestic burglary. Crime displacement resulting from hotspot interventions has been a subject of debate, with approximately a quarter of cases experiencing some form of displacement, the underlying reasons for which remain unclear. This study postulates that the presence of the optimal forager typology of offender may be one contributing factor. To test this hypothesis, we analyze the cumulative crime diffusion and displacement effects of ten optimal forager theory-inspired hotspot interventions employing the weighted displacement quotient (WDQ) technique (Bowers and Johnson, 2003) and the Cambridge harm index (CHI) (Sherman et al., 2016). The findings reveal the interventions' marked efficacy in reducing domestic burglary within response areas. However, this reduction is overshadowed by the substantial spatial and offense displacement they induce, encompassing both crime count and harm. These results provide insights into the proportion of hotspot interventions that trigger crime displacement, and policy implications for the choice and selection of crime reduction strategies. Supported by ecological studies of optimal foragers, we argue that this phenomenon stems from the exceptional motivation of foraging offenders and their inclination toward anti-detection behavior, specifically, relocating to alternative crime areas.